(untitled) (FULafia Journal of Science and Technology, 2020)
The study was carried out to analyze the influence of socio-economic factors on women farmer’s access to agricultural information in Madagali Local Government Area of Adamawa State, Nigeria. The study sought to describe the socio-economic characteristics of rural women farmers and identity the sources of agricultural information available to them, examine the types of agricultural information accessed by them and identity the constraints to access information. Primary data was obtained through purposive and simple random sampling techniques using 180 respondents. Data were analyzed using descriptive statistic logit regression and Likert type rating scale. The findings revealed that age, educational level, extension contact, and societal affiliation are significant in influencing the level of access to agricultural information by the rural women farmers. Poor extension contacts, illiteracy, poverty, crowded household chores and shyness to access information were also identified as some of the constraints to accessing information.